Open radical cystectomy: lessons from the British Association of Urological Surgeons (BAUS) registry - Rossanese, Marta; Subba, Enrica; Giannarini, Gianluca; Inferrera, Antonino; Ficarra, Vincenzo (Translational Andrology and Urology, 2018)
In their recent paper published on the BJU International, Jefferies et al. performed a very interesting analysis of the British Association of Urological Surgeons (BAUS) radical cystectomy (RC) registry capturing approximately 83% of all open RC (ORC) cases performed in England in the period between 2014 and 2015 (1).